PENGARUH PAJAK, MEKANISME BONUS, DAN UKURAN PERUSAHAAN TERHADAP TRANSFER PRICING (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2014-2018) - Endah Ratsianingrum; Fadjar Harimurti; Djoko Kristianto (Universitas Slamet Riyadi, 2020)
This study aims to determine the effect of taxes, bonus mechanisms, and company size on transfer pricing. This type of research is a case study, the type of data used is quantitative data. Datansourcenusednsecondaryndata. The population of.companiesnin thenconsumer goodsnindustry.sectornlisted on the Indonesia Stock Exchange (IDX) in 2014-2018 totaled 42 companies. Samples ofn14 companies for 5 years.with.a.purposive.sampling.method. Collection.techniques.using documen tation and study of literature. The classical assumption test results indicate that all variables have escaped multicollinearity, heteroscedasticity, autocorrelation and normal distribution disorders. Regression analysis of the effects of taxation obtained, and the bonus mechanism have a positive effect, while firmnsize has a negative effect on transfer pricing. T test results, tax (X1), bonus mechanism (X2), and company.size (X3) partiallynhave a significantneffect on transfer pricing (Y). The resultnof F testnshows that the modelnused isncorrect. The coefficient of determination shows the tax variables, bonus mechanism, and company size contribute to the influence of transfer pricing 99,9% and thenremaining 0,1% is influencednby othernvariables notnexamined.